20.1: Invited Paper: Monolithic Full‐color Quantum Dot Nanoring Micro LEDs with Improved Efficiency. (4th October 2019) - Wu, Tingzhu; Sher, Chin-Wei; Chen, Sung-Wen Huang; Lin, Yue; lu, Yijun; Chen, Zhong; Kuo, Hao-Chung
Abstract : Full‐color displays based on micro light‐emitting diodes (µLEDs) have gained expanding research interest. In the study, nano‐ring (NR) structures are fabricated in certain regions on a green LED epitaxial wafer, and the color of NR‐µLEDs can be tuned from green to blue duo to the strain relaxation. In order to improve the luminous efficiency of NR‐µLEDs, atomic layer deposition technique is utilized to deposit an Al2 O3 layer on the sidewall of NR‐µLEDs. As a result, the photoluminescence intensity is significantly improved by 143.7 %. Moreover, red quantum dots (QDs) are sprayed on some blue NR‐µLEDs to achieve the RGB full‐color display. Because QDs are directly contacted with quantum wells of NR‐µLEDs, the color conversion efficiency of QDs can be improved by the non‐radiative energy transfer phenomenon. To further improve the color purity of the red light, a distributed Bragg reflector (DBR) is developed to recycle the excitation light. This study can achieve the full‐color display on a monolithic epitaxial wafer, providing a novel and feasible method for realizing micro‐displays.